2004
DOI: 10.1111/j.0013-8703.2004.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Stored‐product insects in a flour mill: population dynamics and response to fumigation treatments

Abstract: In a wheat flour mill, seasonal trends in stored-product insect trap capture, relationships between trap captures inside and outside the mill, and between pheromone trap capture and product infestation, and the impact of fumigation on pest populations, were assessed. Mark-recapture was used to evaluate the potential for movement of insects outside the mill into the mill. For Plodia interpunctella (Hübner) (Lepidoptera: Pyralidae) and Trogoderma variabile Ballion (Coleoptera: Dermestidae), pheromone trap captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 23 publications
2
86
0
1
Order By: Relevance
“…Campbell & Arbogast, 2004) (route 2) or insects migrate into the semolina from the uncelaned debris in mills and stores (Kucerova et al, 2003;Trematerra & Fiorilli, 2000) (route 3). Hidden infestations of grain kernels from the stores (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Campbell & Arbogast, 2004) (route 2) or insects migrate into the semolina from the uncelaned debris in mills and stores (Kucerova et al, 2003;Trematerra & Fiorilli, 2000) (route 3). Hidden infestations of grain kernels from the stores (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Flourmills are sensitive to the risk caused by many species of pests. Recently, Tribolium beetles ( Figure 1) have emerged as a serious pest problem on a worldwide scale (Campbell & Arbogast 2004). In the Czech Republic, the confused flour beetle (T. confusum) is a persistent pest that is hard to monitor (Stejskal 1995).…”
mentioning
confidence: 99%
“…Tribolium castaneum has long had a reputation for being mostly sedentary and most experiments on movement patterns have been conducted by studying the walking behaviour of the adults (Good, 1933;White, 1981;Campbell & Arbogast, 2004;Campbell et al, 2010ab). Campbell et al (2010a) studied the effects of fumigation (methyl bromide and sulfuryl fluoride) on T. castaneum movement by placing equidistant pitfall traps baited with aggregation pheromone (4,8 dimethyl-decanal) in flourmills for a period of 7 years.…”
Section: Study Species: Tribolium Castaneum Herbst (Coleoptera: Tenebmentioning
confidence: 99%
“…Another study demonstrated that walking beetles were more attracted than flying beetles, to linted cotton seeds than to wheat, both in laboratory and field (Ahmad et al, 2012ab;Ahmad et al, 2013ab). Good (1933) reported that T. castaneum can stay airborne for a maximum of only 20 seconds in the laboratory and many others subsequently accepted that these insects tend to disperse more by anthropogenic means (White, 1981;Campbell & Arbogast, 2004;Drury et al, 2009;Campbell et al, 2010a). But a field study using pheromone baited traps found that these beetles do fly and regularly fly long distances, as they were trapped regularly, and in numbers, at least 1 km from grain storage areas (Ridley et al, 2011).…”
Section: Study Species: Tribolium Castaneum Herbst (Coleoptera: Tenebmentioning
confidence: 99%
See 1 more Smart Citation